Highly Selective and Sensitive Determination of Hg(II) Ions Using Ion Selective Electrodes (ISE) Coated with the BEC4ND1 Ionophore as Membranes - Nasriadi Dali; Seniwati Dali; Armadi Chairunnas; Hilda Ayu Melvi Amalia; Sri Ayu Andini Puspitasari (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2022)
The research on the highly selective and sensitive determination of Hg(II) ions using ion-selective electrodes (ISE) coated with the BEC4ND1 ionophore as a membrane has been successfully carried out. ISE was designed using the membrane composition of the [(BEC4ND1 ionophore : PTCPB : DOS : PVC) (3 : 2 : 60 : 35 % w/w)]. The ESI-BEC4ND1 ionophore has good characteristics where it shows a sensitivity value of 29.933 mV/decade in the Hg(II) ion concentration range of 10-9 - 10-1 M with a limit of detection (LoD) of 10-7 M. The response time obtained is in the range of 4 - 8 minutes with a relative standard deviation (RSD) of 0.548. The ESI-BEC4ND1 ionophore also shows the average value of selectivity coefficient (Kij) < 1. These results indicate that the presence of Zn(II), Cd(II), and Pb(II) ions as interfering ions in the analyte solution does not affect the performance of the ESI-BEC4ND1 ionophore in detecting Hg(II) ions. The ESI-BEC4ND1 ionophore that has been developed shows good selectivity, sensitivity, stability, and reproducibility, so the ESI-BEC4ND1 ionophore is promising to be used as a Hg(II) ion detector in the environment.